Budget Process of North Lombok Regency: Investigating Administration of Social Assistance - Kurniawati, Eka Yuli; Santoso, Budi; Husnan, Lalu Hamdani (International Research Journal of Management, IT & Social Sciences, 2018)
Social assistance is the provision of donations in the form of money/goods from the regional government to individuals, families, groups, and communities that are not continuously and selectively to protect against possible social risks. This study aims to evaluate the implementation and identify factors causing social assistance problems in BPKAD Lombok Utara Regency budget year 2015. A research method in this study using qualitative methods with case study approach. Research data obtained through interviews, observation, and documentation. Data analysis is done interactively using data reduction stages, presenting data, and drawing conclusions or verification. The result of the research shows that (1) the lack of communication and coordination among social assistance management officers in financial administration so that the disbursement of social assistance funds is inconsistent as it is based on the Decree of the Regent of Lombok Utara Regency that is not by the APBD 2015. (2) The difference of understanding of the verifier in the process of administering finance to social assistance management procedures. And (3) the absence of Standard Operating Procedure (SOP) of social assistance management in Lombok Utara Regency. So hopefully in the process of administration of social assistance then BPKAD Lombok Utara Regency needs to improve coordination and thoroughness with the parties concerned and make SOP about social assistance management.